On the origin of exciton formation in dye doped Alq(3) OLEDs - Gomez, J. A.; Castro, F. A.; Nueesch, F.; Zuppiroli, L.; Graeff, Carlos Frederico de Oliveira [UNESP] (Springer, 2012)
Electrically Detected Magnetic Resonance (EDMR) was used to investigate the influence of dye doping on spin-dependent exciton formation in aluminum (III) 8-hydroxyquinoline (Alq(3)) based Organic Light Emitting Diodes (OLEDs) with different device structures. 4-(dicyanomethylene)-2-methyl-6-{2-[(4-diphenylamino)-phenyl]ethyl}-4H-pyran (DCM-TPA) and 5,6,11,12-tetraphenylnaphthacene (Rubrene) were used as dopants. Results at room temperature show significant differences on the EDMR spectra (g-factor and linewidth) of doped and undoped devices. Signals from DCM-TPA and Rubrene dye doped OLEDs showed strong temperature dependence, with signal intensity increasing by 2 orders of magnitude below 200 K for DCM-TPA dye doped OLEDs and increasing by similar to 1 order of magnitude below 225 K for the Rubrene dye doped device, while undoped devices shows almost no temperature dependence. By adding a "spacer" layer of undoped Alq(3) at the recombination zone, changes in bias voltage were used to shift the recombination from doped to undoped region and correlate that with changes in the EDMR spectrum. Our results are indicating that charge trapping on the dopant followed by recombination is the main mechanism of light emission in the investigated devices.